Sex Differences in Anxiety: An Investigation of the Moderating Role of Sex in Performance Monitoring and Attentional Bias to Threat in High Trait Anxious Individuals - Strand, Natalie; Fang, Lin; Carlson, Joshua M. (Frontiers in Human Neuroscience, 2021)
Anxiety disorders are more predominant in women than men, however there is a lack of understanding as to what neurocognitive mechanisms drive this sex difference. Recent investigation has found a potential moderating role of sex in the relationship between anxiety and the error related negativity (ERN)—a component of error-monitoring that is prevalent in high anxiety individuals—such that females display a positive relationship between anxiety/worry and ERN amplitude. We strove to further explore the influence of sex on the relationship between trait anxiety and performance monitoring, specifically with ERN, as well as extend this work to include another hallmark of anxiety, attentional bias to threat. Participants performed a modified flanker task while EEG was recorded to obtain event-related potentials (ERPs). In addition, a dot-probe task was completed to measure attentional bias to fearful faces. We did not find a significant difference in the relationship between attention bias scores and anxiety for female versus males participants, suggesting that attention bias may not be an appropriate measure of sex differences in anxiety. Furthermore, ΔERN and CRN amplitudes were greater in males compared to females. There were no significant associations between ERN or ΔERN with anxiety in both male and female participants. However, there was a significant relationship between CRN amplitudes and trait anxiety in male but not female participants. Given these results, the effect of sex on the relationship between components of performance monitoring— namely the CRN and ERN— and anxiety may be more nuanced than the current understanding.